Repeatability of whole herd lameness scoring: an analysis of a New Zealand dataset - Laven RA; Mason WA; Laven LJ; Müller KR (Taylor and Francis Group, 2024)
AIMS: To assess whether a whole-herd lameness score on a New Zealand dairy farm in spring could predict lameness prevalence on the same farm in summer (and vice versa) and whether a single-herd lameness score could be used to determine whether herd lameness prevalence was < 5% in both spring and summer. METHODS: Prevalence data (proportion of the herd with lameness score ≥ 2 and with score 3; 0-3 scale) from a study where 120 dairy farms across New Zealand were scored in spring and in the following summer were analysed using limits-of-agreement analysis. In addition, farms were categorised as having either acceptable welfare (lameness prevalence < 5% in both spring and summer) or not (lameness prevalence ≥ 5% in either spring or summer or both). The accuracy and specificity of a single, whole-herd lameness score at identifying herds with acceptable welfare were then calculated. RESULTS: The limits-of-agreement analysis suggests that 95% of the time, the prevalence of lameness in summer would be expected to be between 0.23 and 4.3 times that of the prevalence in spring. The specificity and accuracy of identifying a farm as acceptable on both occasions from a single observation were, respectively, 74% and 92% in spring, and 59% and 87% in summer. CONCLUSIONS: A single, one-off, whole-herd lameness score does not accurately predict future lameness prevalence. Similarly, acceptable status (lameness prevalence < 5%) in one season is not sufficiently specific to be used to predict welfare status in subsequent seasons. CLINICAL RELEVANCE: Whole-herd lameness scoring should be used principally as a means of detecting lame cows for treatment. A single whole-herd lameness score by an independent assessor should not be used to determine a herd's welfare status.
Keywords: Locomotion score; dairy cattle; lameness prevalence; predictive ability; welfare assessment